Indices of asthma among atopic and non-atopic woodworkers. Issue 6 (18th May 2004) - Schlünssen, V; Schaumburg, I; Heederik, D; Taudorf, E; Sigsgaard, T
Abstract : Aims: To investigate the relation between wood dust exposure and different indices of asthma among woodworkers and non-exposed subjects. Methods: A total of 302 woodworkers and 71 non-exposed subjects answered a respiratory health questionnaire, underwent a non-specific bronchial provocation test using the Yan method, and received a skin prick test with 12 common inhalant allergens. Subgroups performed repeated peak flow monitoring and underwent a reversibility test. A total of 347 dust measurements among 234 woodworkers were performed with passive dust monitors. Results: The overall geometric mean (geometric standard deviation) exposure to inhalable dust was 0.96 (2.02) mg/m 3 . There was a tendency to increased risk of asthma among atopic woodworkers compared to atopic non-exposed subjects, with ORs between 3.0 (0.8–11.9) (symptomatic BHR) and 1.3 (0.5–4.2) (work related symptoms). In woodworkers, asthma was associated with atopy, with ORs between 7.4 (2.8–19.7) (symptomatic BHR) and 4.2 (2.4–7.7) (asthma symptoms). Asthma was related to dust level, most pronounced for symptomatic BHR among atopics, with OR 22.9 (1.0–523.6) for the highest compared to the lowest dust level. For work related asthma symptoms the association with dust level was seen only for non-atopics. Conclusions: Wood dust exposure was associated with asthma, despite a low dust level compared to other studies. Atopy was an important effect modifier in the association between asthma and wood dust exposure.